MENINGKATKAN KEMAMPUAN PELAFALAN KATA BENDA BAHASA INGGRIS MELALUI MEDIA RECORDER BAGI ANAK LOW VISION - Novil Adriya; Asep Ahmad Sopandi; Tarmansyah - (Jurnal Penelitian Pendidikan Khusus, 2013)
Abstract: This research background by the problems that researchers found in SMALB Negeri 1 Padang, a low vision child's in SMALB class X who have problems in pronouncition of english word, it is first seen when researchers looked at the implementation of the ongoing learning of english in the classroom X in SLB 1 Padang, after apparently observed the child had difficulty in pronounciating the words so when asked pronounciating words the child has difficulty. This research Single Subject Research approach, the AB design and data analysis techniques using visual analysis chart, and graphic. Subjects were low visiom children class X, where the child was difficult to look, pronounciating words per meeting. The results of this study indicate that the recorder Media Figures effective in improving the ability of pronounciating english words. Observations made with the first two sessions, the session before being given intervention baseline (A) conducted seven times observation, the percentage of the ability to pronounciating words on this condition lies in the range of 0%, and 10%. Second, the intervention sessions (B) using the recorder media observation carried thirteen times, ability to recognize shapes percentage points in this condition lies in the range of 30%, 40%, 50%, 50%,60%,60%,70%,70%, 80%, 80%, 100%, 100% .The results obtained in Based on two results it can be concluded pronounciating english words by using recorder media is effective in improving the ability to pronounciating. Suggested the teachers should be able to use the Recorder media Figures in learning english on the child's low vision. Kata Kunci : Low Vision ; kemampuan ; Pelafalan Kata Benda ; Media Recorder